KAJIAN FILOSOFIS PENDIDIKAN PROGRESIVISME DALAM MENGHADAPI TRANSFORMASI DIGITAL PENDIDIKAN - Sari, Dewi Kartika; Khobir, Abdul; Husna, Nadia Amalia; Dini, Rikza; Elysia, Fakikhatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation has brought significant changes to the education system, particularly in learning patterns, the role of educators, and access to learning resources. These changes require a strong philosophical foundation to ensure that the use of technology remains oriented toward the holistic development of learners. This study aims to philosophically examine the relevance of progressivist education in addressing the challenges of digital transformation in education. The research employs a library research method with a philosophical approach through the analysis of various scholarly works related to progressivism and educational technology development. Data were analyzed using content analysis to identify the conceptual relationship between the principles of progressivism and the dynamics of education in the digital era. The findings indicate that the philosophy of progressivism remains highly relevant in supporting twenty-first-century learning, particularly through the principles of student-centered learning, learning by doing, and the development of critical thinking, creativity, communication, and collaboration skills. Furthermore, digital transformation expands opportunities for more flexible, interactive, and contextual learning experiences. However, challenges such as unequal access to technology, low levels of digital literacy, and educators’ readiness continue to hinder its effective implementation. Therefore, progressivism can serve as an important philosophical foundation for developing a humanistic, adaptive, and contextually relevant digital education system.